THE ROLE OF THE CULTURE OF PEACE, ETHNIC TOLERANCE AND MULTICULTURALISM IN EDUCATION OF THE NEW GENERATIONS - Veličković, Dunja (National interest, 2023)
The paper discusses the role of the culture of peace, ethnic tolerance and multiculturalism in the context of contemporary social relations in the Balkans and the world. The focus of consideration is the contemporary conflict research and peace studies, as well as their importance for the education and upbringing of new generations, as well as the role of schools and universities in affirming the value of the culture of peace. The paper emphasizes the importance of the struggle for peace, as a basic prerequisite for the sustainable development of humanity and the survival of the planet. The paper points out the connection of the struggle for peace with a change in development strategy, in the spirit that without global justice there is no global peace in the world (Lula da Silva). Or as the Norwegian scientist Johan Galtung, director of the International institute for peace, rightly says: ’’The fight for different development, as well as the fight for a different peace, must also be led by challenging and even transforming Western cosmology, all those deep-rooted beliefs that they define peace with weapons, and development with money.’’